Borderline serous papillary tumor of the testis - Daphne Fonseca; P Lakshmi Manasa; Rakesh Sharma; Ashwin Giridhar (Wolters Kluwer Medknow Publications, 2020)
Ovarian epithelial type tumor of the testis is a rare entity. Herein, we report borderline serous papillary tumor of the testis in a 37-year-old male, which was clinically suspected to be a testicular malignancy.